Distribusi Logam Berat Dalam Air Laut Dan Sedimen Di Perairan Cimanuk, Jawa Barat, Indonesia - Harmesa; Lestari; Fitri Budiyanto, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Distribution of Heavy Metals in Seawater and Sediments in Cimanuk Estuary, West Java, Indonesia. Increasing economic activities in the north coastal of Java have the potential to contribute to anthropogenic contaminants that threaten the water quality of Cimanuk coastal and estuary in Indramayu. Heavy metal which is one of the wastes from these activities has not been studied in detail. The aim of this study was to determine the distribution of Cu, Pb, Cd, Zn, and Ni in seawaters and sediments of the Cimanuk Estuary. Seawater and sediment samples were collected at 18 stations in May 2017. Seawater samples were extracted using the back extraction method while sediment samples were extracted using acids according to USEPA 3050B. Measurement of heavy metals from seawater extracts or sediments was carried out using Flame Absorption Spectrophotometry according to the USEPA 3050B method. The spatial distribution of heavy metals in seawater and sediments is modeled using ArcGIS® version 10.6.1. The results showed that ranges of metals in seawater : 0,0004 – 0,0038 mg/L (Cu), <0,0001 – 0,0044 mg/L (Pb), 0,0002 – 0,0003 mg/L (Cd), 0,0005 – 0,0119 mg/L (Zn), and 0,0020 – 0,0052 mg/L (Ni). While the metal content in sediments are 12,36 – 54,08 mg/kg (Cu), 6,43 – 15,72 mg/kg (Pb), 0,07 – 0,37 mg/kg (Cd), 64,53 – 85,16 mg/kg (Zn), and 19,66 – 62,85 mg/kg (Ni). Spatial distribution models show that heavy metals in seawater and sediments show identical patterns. High level of metals are generally detected at the stations located closed to the mainland, indicating that heavy metals are enrichment from terrestrial anthropogenic activities.